Variations of Raw Milk Components and Amino Acid Profiles in Different Dairy Buffalo Crossbreds - Rahman, S.M. Rajiur; Islam, Md. Zakirul; Meenongyai, Watcharawit; Hasan, Md. Sayed; Khandakar, Md. Mehedi Hasan; Rana Siddiki, Mohammad Shohel; Islam, Md. Nurul; Harun-ur-Rashid, Md. (Journal of Buffalo Science, 2022)
This study aimed to assess the relationship between milk components and amino acid (AA) profiles among different buffalo crossbreds in Bangladesh. A total of thirty-six (36) lactating buffaloes were selected from Murrah, Nili-Ravi, and Mehsana crossbreds, and they were assigned to 03 groups, each with 12 buffaloes. The total experimental period was 10 weeks, including the initial 10 days of diet adjustment. The results from the experiment revealed that milk protein, fat, and total solids contents of Murrah crossbred was significantly (p<0.05) higher than Mehsana and Nili-Ravi crossbreds. In contrast, the lactose content of all buffalo crossbreds was statistically similar (p>0.05). In the case of milk amino acid contents, all the milk samples entailed a higher concentration of Glutamic acid (0.9-1.00 g/100 g of milk), whereas Cysteine had the lowest concentration (0.02-0.05 g/100 g). The most prevalent essential amino acids were Leucine, Lysine, and Phenylalanine, whereas the most prevalent non-essential amino acids were Glutamic acid, Proline, Asparagine, and Serine. Lysine, Isoleucine, Leucine, Phenylalanine, Cysteine, and Histidine concentrations differed significantly (p<0.05), and at the same time as the other 11 AAs concentrations were found non-significant (p>0.05). The highest Lysine: Methionine ratio observed in Murrah buffalo was about 3.20%, while in Mehsana and Nili-Ravi buffalo was about 2.80 and 2.50%, respectively. Thus, it was evident from the study that the raw milk components and amino acid composition vary considerably in the different lactating buffalo crossbreds. Finally, the compositional data of raw milk may create the way of sustainable use of milk from dairy buffalo crossbreds and improve food and nutrition security, particularly in developing countries.